2018
DOI: 10.1021/acs.chemmater.8b00565
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Nanoparticles with “Light” Property Served as a Multifunctional Probe for X-ray Computed Tomography and Fluorescence Imaging

Abstract: The development of the advanced imaging probe holds the key to the achievement of target imaging and metastasis tracing. The bismuth based nanoprobe has been regarded as the most promising X-ray computed tomography probe due to its largest X-ray attenuation coefficient. Accordingly, the bismuth nanoparticles with controllable size distribution and light weight have been fabricated through a one pot synthesis strategy. The surface modification can be easily conducted with the polyethylene glycol to make the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…Nanomaterials with high atomic numbers (Z) have demonstrated their ability to act as efficient sensitizers of radiotherapy (RT) [1][2][3]. When these high-Z elements are irradiated with X-rays, the result is a high local ionization effect leading to DNA strand breaks and ultimately enhancing the efficacy of RT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials with high atomic numbers (Z) have demonstrated their ability to act as efficient sensitizers of radiotherapy (RT) [1][2][3]. When these high-Z elements are irradiated with X-rays, the result is a high local ionization effect leading to DNA strand breaks and ultimately enhancing the efficacy of RT.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as a metal, elemental Bi strongly absorbs light over a broad spectral range extending to IR, which allows the resulting photothermal heating of elemental Bi nanoparticles by an IR light to be used for photoacoustic imaging as well as for photothermal therapy, which can synergistically enhance radiotherapy [3]. It is also important to note that Bi demonstrates low toxicity, good biocompatibility, and increased cost effectiveness in comparison to other high-Z elements [2]. Furthermore, Bi can also be easily eliminated from the body due to its favorable reactivity and dissolution properties [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Au-DENPs conjugated gadolinium and M-NPAPF-Au demonstrated as great specific nanoprobes to study the internal organs of a mouse for CT/MRI and fluorescence/CT imaging, respectively [42]. Huiting et al [43] introduced Bismuth (Bi) nanoparticles as another dual-modality imaging contrast agent for fluorescence/CT imaging of liver and intestines and tracing of the tumor metastasis. They have shown that Bi nanoparticles can create high CT contrast image and upon the light irradiation, it can emit luminescence photons with diverse color from purple to red.…”
Section: Computed Tomography Scanning (Ct-scan)mentioning
confidence: 99%
“…Most of the current protocols for synthesizing biologically suitable BiNPs cannot be replicated in non-specialized laboratories. Some methods require specialized equipment, such as gamma irradiators [22], laser ablation [23]; or controlled conditions, such as inert atmosphere [24], vacuum [25] or high temperatures [26,27]. Also, some protocols require a long-time synthesis [22], or several intermediate steps [28].…”
Section: Introductionmentioning
confidence: 99%